Analysis Effectiveness Short Passing Accuracy Variation Training In Football: Systematic Literature Review - Ridlo, Ahmad Ari; Adi S, Adi S (UNIVERSITAS NEGERI MAKASSAR, 2025)
This research aims to find out the Variation in the effectiveness of pass-go training on short passing accuracy in football. To ensure process transparency and reproducibility, we reviewed and analyzed published studies according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. The theme of this research as a whole obtained 99. Contains 56 articles, which are then taken from 10 relevant articles. According to the results of literature research, variations in short passing accuracy training in football are very important to improve the technical abilities of players to control the ball and provide passes correctly. This exercise is useful for improving players' passing abilities in various situations and game conditions so that they can face more complex challenges on the field. Because previous research has limitations, it is hoped that future research can build an effective training program.